Pre-Prosecution Efficiency and Islamic Justice: Revisiting the Role of Public Prosecutors in Indonesia - Riyawan, Dara Puspita; Aji Lukman Ibrahim (DIKTUM: Jurnal Syariah dan Hukum, 2024)
This study examines the optimization of the pre-prosecution process in handling criminal cases by the Public Prosecutor at the Attorney General's Office of the Republic of Indonesia. Using normative legal research methods supported by interviews and direct observation, this study aims to identify obstacles in the pre-prosecution process and formulate efforts to resolve them. The results of the study indicate that there are seven main obstacles in the pre-prosecution process, namely: limited coordination between law enforcement agencies, limited time stipulated in the Criminal Procedure Code, incomplete case files, inability of investigators to fulfill the instructions of the public prosecutor, legal uncertainty in the process period, differences in legal interpretation between investigators and public prosecutors, and workload and limited human resources. This phenomenon is illustrated through a case study of the sea fence in the coastal area of ​​Tangerang which shows the complexity of the problems of coordination and legal interpretation in the criminal justice system. As an effort to resolve, this study identifies four main strategies that have been and need to be implemented, namely: the formation of an integrated coordination team, the implementation of joint case titles, the preparation of technical administrative guidelines, and periodic monitoring and evaluation. This study recommends strengthening inter-agency coordination mechanisms, revising criminal procedure law provisions related to time limits, increasing human resource capacity, developing information technology in case handling management, and strengthening internal and external supervision to optimize the pre-prosecution process in the Indonesian criminal justice system.